The Effect of Intravenous Vitamin C on Cancer- and Chemotherapy-Related Fatigue and Quality of Life - Carr, Anitra C.; Vissers, Margreet C. M.; Cook, John S. (Frontiers in Oncology, 2014)
Cancer patients commonly experience a number of symptoms of disease progression and the side effects of radiation therapy and adjuvant chemotherapy, which adversely impact on their quality of life. Fatigue is one of the most common and debilitating symptoms reported by cancer patients and can affect quality of life more than pain. Several recent studies have indicated that intravenous vitamin C alleviates a number of cancer- and chemotherapy-related symptoms, such as fatigue, insomnia, loss of appetite, nausea and pain. Improvements in physical, role, cognitive, emotional and social functioning, as well as an improvement in overall health, were also observed. In this mini review we briefly cover the methods commonly used to assess health-related quality of life in cancer patients, and describe the few recent studies examining the effects of intravenous vitamin C on cancer- and chemotherapy-related quality of life. We discuss potential mechanisms that might explain an improvement in quality of life and also considerations for future studies.